2020
DOI: 10.1007/s42729-020-00271-5
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Spent Coffee Grounds as Media for Stone Pine (Pinus pinea) Seedlings

Abstract: The present study was aimed at determining the influence of adding different amounts of spent coffee grounds (SCG) on germination percentage (GP) and mean germination time (MGT), seedling characteristics, and seedling biomass of different components of containerized 1 + 0 stone pine seedlings. Six different media were prepared including 100% conventional media, 100% sand, 10% SCG + 90% sand, 20% SCG + 80% sand, 30% SCG + 70%, sand and 100% SCG. While GP is 90% in the media where the SCG ratio is 10%, GP values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
(60 reference statements)
0
3
0
1
Order By: Relevance
“…Limited plant growth may mainly be attributed to the SCG composition of caffeine, polyphenols, and tannins [16,22], which have been identified to be not only phytotoxic but also ecotoxic [37]. Several authors have reported toxicity effects with different doses of SCG in lettuce (2.5, 10%) [19] and stone pine seedlings, which are also rich in polyphenols and tannins, at 10, 20, 30, and 100% [38]. In contrast, some authors describe enhanced dry weight when plants are found in sandy low mineral soil [39,40].…”
Section: Effects On Plant Growthmentioning
confidence: 99%
“…Limited plant growth may mainly be attributed to the SCG composition of caffeine, polyphenols, and tannins [16,22], which have been identified to be not only phytotoxic but also ecotoxic [37]. Several authors have reported toxicity effects with different doses of SCG in lettuce (2.5, 10%) [19] and stone pine seedlings, which are also rich in polyphenols and tannins, at 10, 20, 30, and 100% [38]. In contrast, some authors describe enhanced dry weight when plants are found in sandy low mineral soil [39,40].…”
Section: Effects On Plant Growthmentioning
confidence: 99%
“…According to the literature, fertilizing with CH and SCG is a good cropping practice to contribute to the sustainability of agriculture [95,96]. In the work of Zoca et al, CP, CH, and composted CH were evaluated as fertilizers, since they contain the important mineral potassium (K) [97].…”
Section: Fertilizersmentioning
confidence: 99%
“…The use of CH and their biochar as soil amendments could reduce fertilization costs and prevent environmental degradation by recycling the nutrients that would be lost by leaching or runoff from the stored residue for prolonged times [97]. Moreover, SCG have been used to store stone pine seedlings, and it was found that mixtures of 10-20% SCG and sand increased the germination time and enhanced the characteristics of the seedlings by supplementing K, N, Mg, and P [95]. Similarly, water extracts from SCG and tea leaves have been used as the primer agents (growth inducers) of pepper [96].…”
Section: Fertilizersmentioning
confidence: 99%
“…Além disso, o resíduo do pó de café é rico em compostos orgânicos, a exemplo de ácidos graxos, lignina, celulose, hemicelulose, entre outros, fazendo parte também da composição desse resíduo, alguns minerais, tais como potássio, fósforo e magnésio, com predominância do potássio, os quais podem contribuir para a nutrição das plantas. (CALISKAN et al, 2020).…”
unclassified